A Case Report of a child with hallucination and aggressive behavior due to AntiNMDAR encephalitis (The Review of Diabetic Studies, 2025)
Background: Anti-NMDAR encephalitis is an immune-mediated neuroinflammatory disease characterized by autoantibodies against the GluN1 subunit 2B (NR2B)/NMDA subunit 2A (NR2A) subunits of the NDMA receptor in the hippocampus, causing the symptoms. Case Report: We report a case a13-year-old girl, previously healthy, presented with a history of auditory and visual hallucinations; she saw some of her family members in the room who were not present, and she fought with them; she said they wanted to fight me, attack me, please stop them. She is pitting her tongue, moving it constantly inside and outside her mouth (orofacial dyskinesia), and making abnormal movements with her lips for one day. On the second day of admission, the patient developed aggressive behavior, such as pitting her hands, pulling her hair, throwing objects, seeing people not around, screaming, repeating words, and falling asleep. Result: The patient initially received ceftriaxone and acyclovir for ten days, olanzapine, and benzodiazepine regularly. The trial of the Prednisolone dose was followed by methylprednisolone, thiamine, biotin, and pyridoxine.  EEG showed many Delta brush waves that suggested anti-NMDAR autoimmune encephalitis and NMDA Receptor Abs CSF was 1:16; Glutamate receptor (Type NMDA) IgG abs are detectable in cases of limbic encephalitis. The plan was to start a plasma pheresis with plasma protein for five days, followed by IVIG and Rituximab infusion after virology and quantifiers, which came negative.Conclusion: Anti-NMDAR encephalitis can be easily diagnosed using serum or CSF sample testing. An index of suspicion should be raised in children presenting with personality changes, abnormal movements or postures, seizures, autonomic instability, or hypoventilation. Management may also be clinically challenging as it involves treating both the cause and the symptoms. A continuous follow-up by the rehabilitation and neurology team is essential. Interdisciplinary communication and collaboration are quintessential to good patient outcomes with this condition.